ERGONOMIC WORK FACILITY DESIGN USING ANTHROPOMETRIC DATA - Kusumadewi, Intan; Budiman; Taufiqur Rohman, Rofi (Jurnal Mekanika dan Manufaktur, 2024)
This study aims to design an ergonomic study table based on students' anthropometric data to reduce the risk of musculoskeletal injuries. Anthropometric data, such as sitting elbow height, knee height, thigh length, and hand reach, were collected from 121 students using an anthropometer. In addition, musculoskeletal complaints were evaluated using the Nordic Body Map (NBM). Ergonomic risks were assessed using REBA (Rapid Entire Body Assessment) and RULA (Rapid Upper Limb Assessment) methods to identify non-ideal work postures. The results of the analysis showed that the current working posture of the students was in the high to very high risk zone, with a final REBA score of 9 and RULA of 8. Based on these results, an ergonomic study table was designed with adjustable height features (60-72 cm), 62 cm table width, and 124 cm table length. This design refers to anthropometric data with the 5th to 95th percentile range to ensure comfort and compatibility with various student body dimensions. This ergonomic study table design is expected to reduce the risk of musculoskeletal injuries, increase productivity, and create a healthier and more comfortable learning environment for students. Design validation through hands-on testing is a recommendation for further research.